Detection of dioxins Trichloro dibenzo-p-dioxins and Trichloro dibenzofurans in beef with Gas Chromatography Tandem Mass Spectrometry - Indraningsih . .; Yulvian Sani (Jurnal Ilmu Ternak dan Veteriner, 2014)
This study is to investigate the residue level of TCDDs/TCDFs in beef collected from Animal Slaughter Houses in Giwangan (Yogyakarta), Klaten (Central Java) and Kupang (East Nusatenggara). Residue of persistent organic pollutants (POPs) was also analysed with GC-ECD, and dioxins with GC-MSMS. Fifty samples were collected form Giwangan (20), Klaten (15) and Kupang (15). Results shows that POPs were detected in beef samples including aldrin, dieldrin, DDT, endrin and heptachlor. The highest total residues of POPs were detected in beef from Giwangan (Yogyakarta) at 93.11 hg/g, followed by Klaten (17.79 hg/g) and Kupang (12.87 hg/g). Residues of POPs were below the maximum residue limit stated by the SNI 7313: 2008. Average of total TEQ for TCDDs/TCDFs in beef from Giwangan was 13,624.38 rg/g with a range between 4,496.66 to 20,642.40 rg/g was higher than that from Kupang at 1,623.98 rg/g with a range between 0.83 to 6,471.07 rg/g. On the other hand, dioxins were not detected in beef from Klaten. The total TEQ of TCDDs/TCDFs in beef samples from Giwangan was 54,497.52 rg/g and Kupang was 6,495.9 rg/g. These results indicated that there was an association between the presence of endrin and heptachlor with the presence of TCDDs/TCDFs residues in beef that this is may be new information for further studied.